Understanding Local Tradition of Pamali Banjar and Integration of Islamic Education Values : Memahami Tradisi Lokal Pamali Banjar dan Integrasi Nilai-Nilai Pendidikan Islam - Qutni, Darul; M. Noor Fuady (Interdisciplinary Explorations in Research Journal, 2024)
Islam is an identity of Banjar people. In their daily life, Banjar people also knowand believe in pamali. On the other hand, pamali is not allowed by Islamic religion. Is there any pamali in Islam? The objective of this study is to describe pamali originating from Islamic teachings such as the Qur'an and hadith. This research uses decriptive qualitative method. The results of this study prove that the Banjar pamali is partly derived from the Qur'an, and hadith, and the words of ulama. The pamali from the teachings of Islam is in the way of eating and drinking, sleeping, farming, In the five pillars of Islam and Islamic teachings, pamali is practiced and believed by people. The pamali taken from the Qur'an, hadith, and the words of ulama do not make people shirk